A Leader's Guide to Designing High Performing Quality Management Systems The 7 Keys That Solve, Achieve, Sustain, and Transform Organizational Outcomes in High-Risk Environments. - Bedgood, Casey (Oxford : Productivity Press, 2024)
The intended audience for this book includes but is not limited to: top executives, governance members, leaders of any rank, thought leaders, strategists, students, performance improvement leaders, change agents, teachers, and anyone interested in quality, improvement, strategy, and leadership.
Cover -- Half Title -- Title Page -- Copyright Page -- Contents -- About the Author -- Introduction -- Chapter 1: Common Misperceptions of Quality Management System (QMS) -- Chapter 2: Crucial Conversation Talking Points -- Chapter 3: The QMS Assessment -- Chapter 4: The QMS Structure -- Chapter 5: The QMS Process -- Chapter 6: Measuring QMS Success -- Chapter 7: Case Study: Is QMS a Risky Proposition? -- Conclusion -- Index
Description based upon print version of record.
Keywords: Quality control -- Management; BUSINESS & ECONOMICS / Total Quality Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Leadership